GAMBARAN PENGETAHUAN ORANG TUA TENTANG IMUNISASI MEASLES RUBELLA DI MADRASAH IFTIDAIYAH AL-KAUTSAR PALEMBANG TAHUN 2019 - Mirsa Hardianti; Khoirin Mugiman (STIK SITI KHADIJAH PALEMBANG, 2019)
Background:according to the world health organization (WHO) Indonesia’ Immunization program has a goal of reducing Immune-preventable disease and mortality rates. Immunization efforts have been held in Indonesi since 1956. Beginning in 1977, Immunization efforts were expanded into an immunization development program in the prevention of immunization of disease infections (pd3i) such as immunodeficiency, diphtheria, pertusis, measles, tetanus, polio, hepatitis, pneumonia, rotavirus, congenital rubella syndrome, human papillomas. The goal of this studyis to find out what parent’s awareness of the immunization of emergency Bella in the madrassa ibtidayah al-kautsar palembang in 2018. This method of research uses the quantitative descriptive research design, the sample was taken using the 34-parent sampling of madrasah iftidaiyah al-kautsar who is nagaswidak area of labor center. Data analysis using a Univariate analysis, the study was performed in January 2019. The vast majority of 34 respondents were known to have 20 ( 58,8%) when 11(32,4%) had a good knowledge of immunization, while 11(32,4%) had sufficient knowledge and 3(8,8%) had little knowledge. Suggestions: it is hoped that studies could use more varied variables and cover more broader research, so tah research on disease disease and disease could be constantly improved.